ILegal Certainty and Consumer Protection in Halal Certification of Children's Snacks Containing Pork: A Sharia Economic Law Perspective - Muhamad Shofiyudin; Cucu Susilawati; Dian Herdiana; Khalid Bhatti, Omar (Universitas Islam Negeri Raden Intan Lampung, 2026)
The incident in the case of children's snacks certified halal but containing pork elements raises serious issues related to the legal certainty of halal certification and consumer protection, especially Muslim consumers and children. In this condition, a more in-depth study is needed regarding the governance of halal certification and the implemented oversight mechanisms, especially regarding food products circulating in the market and consumed by the public or Muslim consumers. This study aims to analyze the legal certainty of halal certification and consumer protection in the case of children's snacks contaminated with pork in Indonesia from the perspective of Sharia Economic Law and the Consumer Protection Law. The research method used is qualitative with an empirical juridical approach and analytical descriptive method, through interviews with BPJPH and consumers as well as a literature study of related laws and regulations and fatwas. This study fills the gap in the study regarding the legal certainty of halal certification for products that have obtained halal certification but are later proven to contain pork elements. The research findings indicate that the weakness of the traceability system, post-halal certification supervision of products that have been certified but are proven to contain pork elements and internal halal audits of companies are the main factors that cause changes or non-conformities in raw materials not to be detected early. As a result, non-halal elements can enter the production process and are only revealed after laboratory testing is carried out on products circulating in the community. From the perspective of Sharia Economic Law, this condition reflects a violation of the principles of trust, honesty, and the prohibition of tadlis and gharar, while in the Consumer Protection Law, this incident is a violation of consumers' rights to correct information and a sense of security.